Potensi Ekstraktif Kayu Arang (Diospyros sp.) sebagai Agen Antifungal terhadap Jamur Pelapuk Kayu Trametes versicolor: Potential of Diospyros sp. Wood Extract as an Antifungal Agent against the Wood-Decaying Fungi Trametes versicolor - Ainun Zalsabila; Syahidah; Sitti Hardianti Suaib; Astuti Arif (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
In recent years, there has been growing research interest in the use of plant extracts as candidate natural wood preservatives. Diospyros sp. wood, a member of the family Ebenaceae, is known to contain extractive compounds with potential antifungal activity. This study aimed to evaluate the potential of Diospyros sp. wood extractives as antifungal agents against the white-rot fungus Trametes versicolor, which is recognized as one of the economically important wood-decaying fungi. Extraction of bioactive components was carried out using acetone and methanol, followed by fractionation with three solvents of different polarity to separate groups of compounds based on their polarity. The analysis indicated that the extractive components of Diospyros sp. wood are dominated by polar compounds. In vitro antifungal assays against T. versicolor showed no detectable inoculum growth on samples treated with Diospyros sp.extracts, either from sapwood or heartwood, indicating their effectiveness as natural wood preservatives. The Antifungal Activity (AFA) value reached 100%, demonstrating that Diospyros sp. wood extractives effectively inhibited the growth of white-rot fungi and conferred a high level of resistance to wood decay. Keywords: Antifungal Activity, Diopyros sp., Extractives, Natural Preservative, White Rot Fungi, Trametes versicolor